1990
DOI: 10.1099/00221287-136-1-147
|View full text |Cite
|
Sign up to set email alerts
|

31P NMR studies on the effect of phosphite on Phytophthora palmivora

Abstract: 31P N M R spectra were obtained from perchloric acid (PCA) and KOH extracts of Phytophthora pdmivora mycelium. Signals indicating the presence of large amounts of short-chain plyphosphate were observed in the spectra of PCA extracts of mycelia grown under both low (0.1 mM) and high (10 mM) phosphate conditions. The mean chain length of polyphosphate was calculated from the relative areas of signals arising from terminal and internal P nuclei in the polyphosphate chain. The small amount of plyphosphate evident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…This view is corroborated by the observation that 0.1 to 3 mM Phi markedly inhibits the growth of Phytophthora mycelia in sterile culture (Smillie et al, 1989). 31P-NMR spectroscopy has revealed that Phi perturbs P metabolism in Phytophtkova by causing a massive accumulation of poly-P and PPi but not sugar-P or nucleotide-P pools Niere et al, 1990Niere et al, , 1994). Phi's toxicity in Pkytophtkora sp.…”
Section: ~ -supporting
confidence: 60%
See 1 more Smart Citation
“…This view is corroborated by the observation that 0.1 to 3 mM Phi markedly inhibits the growth of Phytophthora mycelia in sterile culture (Smillie et al, 1989). 31P-NMR spectroscopy has revealed that Phi perturbs P metabolism in Phytophtkova by causing a massive accumulation of poly-P and PPi but not sugar-P or nucleotide-P pools Niere et al, 1990Niere et al, , 1994). Phi's toxicity in Pkytophtkora sp.…”
Section: ~ -supporting
confidence: 60%
“…Poly-P, which rarely occurs in higher plants (Harold, 1966;Jeffrey, 19681, was also undetectable in the Phi-treated B. nigra seedlings. In these respects, the effects of Phi on B. nigra are very different from those that it elicits in Phytophthora sp., in which approximately 1 mM Phi causes massive accumulation of PPi and poly-Ps and a significant increase in Pi Niere et al, 1990Niere et al, , 1994.…”
Section: Effect Of Phi On Protein Content and Activities Of Pepase Pmentioning
confidence: 99%
“…Phi acts as a systemic fungicide against several species of fungi (Guest and Grant, 1991). Its toxicity appears to be due to a combination of factors, including decrease in total adenylate pool, accumulation of poly-and pyrophosphates, and inhibition of several enzymes involved in the glycolytic and pentose Pi pathways Niere et al, 1990Niere et al, , 1994Guest and Grant, 1991;Barchietto et al, 1992;Stehmann and Grant, 2000). Furthermore, addition of Phi to Pi-starved yeast resulted in reduced levels of sugar Pis, pyrophosphates, and polyphosphates, and it also inhibited Pi stress-repressible acid phosphatase (McDonald et al, 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have identified alterations to fungal metabolism Niere et al, 1990Niere et al, , 1994Barchietto et al, 1992) and changes of morphology (Jiang, 1990;Jiang & Grossmann, 1992). These changes might account for both direct fungal inhibition and modification of the interactions between host and parasite.…”
Section: Introductionmentioning
confidence: 99%